“Circulations” and Self-Transcendence: A Comparative Study of Emerson and Zhuangzi - Meng Jia (Religions)
In this article, I begin with the topic of “circulations”, conducting a comparative analysis of the similarities and differences in Emerson’s and Zhuangzi’s philosophies regarding “circulations” as the mode of cosmic generation and operation, as well as the relationship between “circulations” and self-transcendence. Furthermore, I explore the practical paths to achieve self-transcendence via circulations based on these two aspects. Specifically, both Emerson and Zhuangzi regard “circulations” as the fundamental way of cosmic generation and operation. However, Emerson emphasizes the directionality of “circulations”, where God generates all things through “emanation”, and all things return to God through “ascent”. In contrast, Zhuangzi emphasizes the characteristics of the Dao in generating all things, including its “cyclic repetition” (xun huan wang fu 循环往复) and “creating myriad forms” (zhi qi wan shu 制器万殊). The “Dao” that generates these “circulations” itself does not possess morality or divinity. Both of them believe that individuals can achieve self-transcendence by aligning with “circulations”. Regarding the specific practical paths, Emerson suggests that we can return to God through revelation, specifically via nature, poets, art, and vocation. On the other hand, Zhuangzi believes that we can achieve unity with the Dao by “following the Dao”, specifically through the life-nurturing method of “following the Du as a principle” (yuan du yi wei jing 缘督以为经) and the spiritual cultivation methods of “emptiness of mind-heart and selflessness” (xinzhai 心斋) and “sitting in oblivion” (zuowang 坐忘).